A free boundary problem for a nonlinear diffusion-convection equation: A free boundary problem for a nonlinear diffusion-convection equation - Rasulov, M.S.,; Umirkhanov , M.T. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Free boundary problems are of great importance, both physically and mathematically. Free boundary problems are boundary value problems for partial differential equations where an unknown moving boundary must be determined. In this paper, we formulate a free boundary problem for a nonlinear diffusion-convection equation namely Rosen-Fokas-Yorstos equation [1]. This equation describes fluid diffusion with convective